Design of a Low-Profile Dual-Polarization Wideband Semi-Flexible Antenna - Ankang Liu; Jian Lu; Peng Khiang Tan; Theng Huat Gan (IEEE Access)
This paper proposed a low-profile dual-polarization wideband inverted-F fed stacked-patch semi-flexible antenna. The proposed antenna features a stacked-patch on the top PCB layer and two orthogonal inverted-F feed structures on the bottom PCB layer. Flexibility is achieved through the thin, flexible bottom PCB layer, while the rigid top PCB layer can be arranged to prevent collisions between adjacent cells, allowing the array to bend easily. Two orthogonal inverted-F feeds share the same flexible PCB layer, enabling a low-profile dual-polarization antenna design. Polarization in x-direction is achieved using the single-ended inverted-F feed, while polarization in y-direction is achieved using the differential-ended inverted-F feed. Simulations were conducted to examine the impact of bending the flexible bottom PCB layer on the antenna performance. Key parameters of the proposed antenna were studied and a prototype was fabricated to validate the design concept. Measurement and simulation results are in good agreement. The thickness of the proposed antenna is $0.067~λ $ at the lowest operating frequency and the bandwidth is 15%. Measured isolation between the two ports is 26 dB.